All in this together: exploring South African social worker’s experiences of shared trauma under Covid-19 - Maier, Kathrin (My University, 2022)
Covid-19 has taken a great toll on people’s mental health worldwide. The present study investigates experiences of shared trauma among South African social workers in the mental health field, who were categorized as providing “essential” services during periods of lockdown. Adapting critical phenomenology as research methodology, nine in-depth, semistructured interviews were conducted, transcribed true verbatim, and analyzed through Fairclough’s socio-cultural model of critical discourse analysis. Participants were all employed at the same organisation providing mental health services around the city of Johannesburg. Sampling followed a purposive strategy while social workers were selected according to their willingness and availability. The findings of this study contribute to existing research on shared trauma by highlighting how participant’s meaning-making is shaped by discourses of survival and service, as well as individual and structural failure. Possibilities of growth and change are also explored and point to pre-existing challenges that have been exacerbated by the impact of the pandemic. Here, the study sheds light on how social workers in the mental health field navigate their experiences of being exposed to similar stressors as their clients. A second-level analysis focusing on the contextual and structural aspects of participant’s lived experiences further revealed the de-politicizing effect of a bio-medical and neoliberal discourse. Professionalism was identified as a potential source of hegemony and resistance if extended trough trauma-informed and culturally sensitive perspectives. Finally, recommendations are given on how social workers can realign with their commitment to social justice, while tackling structural barriers the profession and mental health care users are currently facing.
A dissertation submitted in partial fulfilment of requirements of degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2022